EFFECT OF SALES PROFITABILITY AND GROWTH ON STOCK PRICE - Siti Nuridah; Rony Marthin Sitohang; Ari Sarah Sofura; Elda Sagitarius (Jurnal Ekonomi, 2022)
This study aims to examine the effect of ROE and sales growth on stock prices (Case Study in Manufacturing Companies in the Consumer Goods Industry Sub Sector Listed on the IDX in 2019-2021). The research sampling technique uses a purposive sampling technique with the following criteria: (1) Manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period. (2) Manufacturing companies in the consumer goods industry sector which display annual financial reports for the 2019-2021 period. (3) Manufacturing companies in the consumer goods sector that have complete data and information needed for research during 2019-2021. (4) Manufacturing companies in the consumer goods sector that have non-negative net profits during 2019-2021. The analytical method used is multiple linear regression, hypothesis testing using the t-test to test the partial regression coefficients and the F-test to test the simultaneous coefficients. In addition, the variables have also been tested using the classical assumption test. The research results on the t-test show that the variable Return On Equity (ROE) partially has no significant effect on stock prices. While Sales Growth partially has a positive and significant effect on stock prices. The results of the F test show that the variable Return On Equity and sales growth simultaneously have a positive and significant effect on stock prices. The regression estimation results show that the predictive ability of all independent variables on stock prices is 10.8%, while other factors outside the study influence the remaining 89.2%.